2014
DOI: 10.1063/1.4897503
|View full text |Cite
|
Sign up to set email alerts
|

First principles assessment of helium trapping in Y2TiO5 in nano-featured ferritic alloys

Abstract: oxides are the major features that provide high strength and irradiation tolerance in nano-structured ferritic alloys. Here, we employ density functional theory to study helium trapping in Y 2 TiO 5 . The results suggest that helium is more deeply trapped in Y 2 TiO 5 compared to Y 2 Ti 2 O 7 . Helium occupies open channels in Y 2 TiO 5 , where it weakly chemically interacts with neighboring oxygen anions, and results in less volume expansion compared to Y 2 Ti 2 O 7 , reducing strains in the iron matrix. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…The reason that spherical amorphous oxides form internal voids, while faceted crystalline oxides in NFAs form interface bubbles is not understood. The fact that helium injection promotes internal void formation in the oxide particles means that helium must dissolve in the particles, consistent with first principles calculations on a variety of other oxides [30,31]. As noted earlier, the Y/Al ratio between the ODS particles in the NIO versus ISHI side of the foil differs considerably, but the relationship to the amorphization and difference in internal voids is unclear.…”
Section: Characterization Of the Oxide Particlessupporting
confidence: 81%
“…The reason that spherical amorphous oxides form internal voids, while faceted crystalline oxides in NFAs form interface bubbles is not understood. The fact that helium injection promotes internal void formation in the oxide particles means that helium must dissolve in the particles, consistent with first principles calculations on a variety of other oxides [30,31]. As noted earlier, the Y/Al ratio between the ODS particles in the NIO versus ISHI side of the foil differs considerably, but the relationship to the amorphization and difference in internal voids is unclear.…”
Section: Characterization Of the Oxide Particlessupporting
confidence: 81%
“…Various studies have suggested that the nano-oxides might range from coherent solute-enriched clusters or Guinier-Preston-type zones, to near-stoichiometric complex oxides, that are primarily the pyrochlore Y2Ti2O7 and to a lesser extent orthorhombic Y2TiO5 (and/or even less some other possible oxides in crystalline and even amorphous phases) [16,[22][23][24][25][26][27][28][29][30][31]. In our previous work [32,33], we have shown from first principles that helium in NFAs partitions and is deeply trapped in both Y2Ti2O7 and Y2TiO5 oxides. The Boltzmann partitioning factors at 773K were estimated to be in the order of ~10 10 and 10 8 for bulk Y2TiO5 and Y2Ti2O7, respectively.…”
Section: Introductionmentioning
confidence: 85%
“…[17][18][19][20] Various first-principles calculations have been performed in order to investigate the confinement of helium to the oxide NCs, but primarily, these have taken place in either bulk oxide, or bulk BCC Fe. [21][22][23][24][25][26] Results from these investigations have shown that the formation energy associated with creating a helium interstitial is significantly higher in BCC Fe (B4.5 eV) 26 than in the oxides (B1-1.5 eV). [21][22][23][24][25][26] Additionally, the investigations have revealed that the migration barrier of helium in the Fe matrix is extremely low (0.07 eV) 26 compared to the oxides (0.5-1.5 eV), 22,24 where the constituent oxygen atoms play a key role in prohibiting helium migration.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25][26] Results from these investigations have shown that the formation energy associated with creating a helium interstitial is significantly higher in BCC Fe (B4.5 eV) 26 than in the oxides (B1-1.5 eV). [21][22][23][24][25][26] Additionally, the investigations have revealed that the migration barrier of helium in the Fe matrix is extremely low (0.07 eV) 26 compared to the oxides (0.5-1.5 eV), 22,24 where the constituent oxygen atoms play a key role in prohibiting helium migration. A recent investigation of the Y 2 Ti 2 O 7 /Fe interface found that there are low vacancy formation energies and helium defect formation energetics similar to the bulk oxides, which promotes the sequestration of helium from the matrix to the interface.…”
Section: Introductionmentioning
confidence: 99%